Patterned Ground - Ballantyne, C. K. (Elsevier Inc., 2013)
Patterned ground is terrain exhibiting surface patterning, primarily in the form of circles, polygons, irregular networks, or stripes. Sorted patterns are defined by alternating soil and clasts, and nonsorted patterns by microrelief or vegetation. Most patterns form through recurrent ground freezing and thawing and are initiated by differential (laterally nonuniform) frost heave. Small sorted forms are produced by shallow differential frost heave or needle-ice heave. Large sorted patterns are probably initiated by differential frost heave, but may develop through buoyancy-driven soil circulation during thaw. Frost polygons develop through recurrent thermal contraction cracking of permafrost and freezing of meltwater in cracks. Earth hummocks and vegetation-defined nonsorted circles are probably initiated by differential frost heave, though buoyancy-driven soil circulation and other mechanisms may contribute to their subsequent development.